Hukum Pembayaran Uang Charge Sewa Mobil Perspektif Fatwa DSN MUI Nomor 112/DSN-MUI/IX/2017 Tentang Akad Ijarah - Riska, Yosanda Faniya; Permata, Cahaya (Fakultas Syariah INSURI Ponorogo, 2022)
There are many problems in car rental services, one of the problems is excess rental time which eventually causes additional fees or charges. The purpose of this study is to find out how the agreement is between the tenant and the lessor and how the law does not pay the Charges from the perspective of the Fatwa of the National Syari'ah Council Number 112/DSN MUI/IX/2017 Concerning Ijarah Contracts. The research method used is empirical legal research. The results of the study show that the law of payment of Charges on car rental overtime due to car damage from the perspective of the Fatwa of the National Syari'ah Council Number 112/DSN-MUI/IX/2017 concerning Ijarah Contracts is mandatory because it has been agreed upon in the contract according to the fatwa regarding Ijarah. So that the obligation to pay Charge money is a form of agreement in the agreed contract related to excess time.